2021
DOI: 10.21037/atm-20-4783
|View full text |Cite
|
Sign up to set email alerts
|

Poor consistency between reflux symptom index and laryngopharyngeal pH monitoring in laryngopharyngeal reflux diagnosis in Chinese population

Abstract: Background: It is unknown whether the reflux symptom index (RSI) can replace pH monitoring as a diagnostic tool for laryngopharyngeal reflux (LPR) in Chinese people. The relationships between reflux parameters and LPR symptoms also require further research.Methods: A total of 216 Chinese patients underwent laryngopharyngeal pH monitoring and filled out an RSI questionnaire. Laryngopharyngeal pH monitoring indicated a diagnosis of LPR for patients with 7 or more episodes of reflux or a reflex area index (RAI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…This study found that the consistency between the RSS and 24 h MII‐pH was comparatively high (kappa value = 0.663), with a sensitivity of 92.8% and a specificity of 71.4%. However, RSI had a general consistency with 24 h HEMII‐pH (kappa value = 0.213) and a sensitivity of 48.2% but specificity is 80.9%, a result similar to other studies 18,19 . The extra inclusion of ENT, digestive, and respiratory symptoms in the RSS allows for a more comprehensive assessment and make patients a clearer understanding of the frequency and severity of symptoms.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study found that the consistency between the RSS and 24 h MII‐pH was comparatively high (kappa value = 0.663), with a sensitivity of 92.8% and a specificity of 71.4%. However, RSI had a general consistency with 24 h HEMII‐pH (kappa value = 0.213) and a sensitivity of 48.2% but specificity is 80.9%, a result similar to other studies 18,19 . The extra inclusion of ENT, digestive, and respiratory symptoms in the RSS allows for a more comprehensive assessment and make patients a clearer understanding of the frequency and severity of symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…However, RSI had a general consistency with 24 h HEMII-pH (kappa value = 0.213) and a sensitivity of 48.2% but specificity is 80.9%, a result similar to other studies. 18,19 The extra inclusion of ENT, digestive, and respiratory symptoms in the RSS allows for a more comprehensive assessment and make patients a clearer understanding of the frequency and severity of symptoms. The RSS expands the scope of symptom screening and is more sensitive and consistent than the RSI, but as a result, the specificity of the RSS is inevitably less than that of the RSI.…”
Section: Symptom Characteristics In Lpr Patientsmentioning
confidence: 99%
“…Despite RSI being developed as a tool for LPR symptoms [ 63 ], there is a lack of agreement between its score and laryngopharyngeal pH monitoring [ 79 ]. The findings of this study support the fact that symptoms reflected in the RSI are not always associated with LPR [ 80 ] and may be related to other etiologies including LSD.…”
Section: Discussionmentioning
confidence: 99%
“…Vance et al observed that oropharyngeal pH monitoring correlated better with total patient symptom scores including cough, heartburn, burping, and throat clearing compared with HEMII-pH. The findings of Vance et al do not corroborate those of Weitzendorfer et al who observed that elevated Dx-pH measurements did not show significant correlation with either pH–impedance monitoring features, RSI, RFS, and saliva pepsin measurements [ 59 ]. However, irrespective to the pH study device, the correlation between pH study, symptoms, and findings remains controversial according to many studies that could not demonstrate an apparent relationship between the intensity of symptoms and the magnitude and patterns of hypopharyngeal reflux events [ 1 , 60 ].…”
Section: Diagnosis Of Reflux and Place Of Ph Studymentioning
confidence: 95%